Investigation of wear of rollers of Belarussian metallurgical plant mill - A. B. Steblov; V. I. Timoshpolsky; V. V. Filippov; V. A. Tischenko; E. A. Steblova (Литьë и металлургия, 2000)
The outcomes of the reseach, formula for account of wear of rollers are indicated in this aniele depending on the factors of the cross-section of hire and chemical structure of steel.